Criteria-Based Management Of An Osteoarthritis Knee In Nk Health Clinic: A Case Report - Catherine Hermawan Salim; Yurita Mailintina; Astrid Komala Dewi (Sean Institute, 2024)
Osteoarthritis is a degenerative joint disease which has a characteristic chronic, progressing slowly when all of the structure of the joint changes pathologically. Role of physiotherapist is appropriate to the problem in the osteoarthritis case based on the results of physiotherapis examination which includes an assessement, diagnosis, planning and evaluation for increasing mobility of movement and functional activities in patient with osteoarthritis of knee. Case description: Mr.J 60 years old complaints of knee pain that has been felt about 2 years ago. After doing a physiotherapis examination, he has a diagnosis osteoarthritis of knee. The diagnosis of knee osteoarthritis is based on the physical examination and supporting examination. According to result of x-ray showed Mr.J has grade III osteoarthritis on the right side knee where moderate osteophyte, deformity of the bone tip cracked joints narrowed. Results: After of the physioterapis treatment program is carried out for 4 weeks with 2- 3x/week. The patient has experienced a change from relaxation and in carrying out daily activities such as going up and down stairs,sitting and squatting. Conclusions: All of the goals or outcome measure can be achieved by management of physiotherapis with applying various aspects appropriately and spesific.